2005
DOI: 10.1007/s00345-005-0501-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of a combination of sabal and urtica extract for lower urinary tract symptoms—a placebo-controlled, double-blind, multicenter trial

Abstract: The efficacy and tolerability of a fixed combination of 160 mg sabal fruit extract WS 1473 and 120 mg urtica root extract WS 1031 per capsule (PRO 160/120) was investigated in elderly, male patients suffering from lower urinary tract symptoms (LUTS) caused by benign prostatic hyperplasia in a prospective multicenter trial. A total of 257 patients (129 and 128, respectively) were randomized to treatment with PRO 160/120 or placebo (127 and 126 were evaluable for efficacy). Following a single-blind placebo run-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 17 publications
0
50
1
1
Order By: Relevance
“…This plant is also commonly known in Roman as Nettle and in Jordan as Qurraus [1,2] . For decades, crude extracts of plant species of U. pilulifera have long been used in many countries around the world as a traditional medicine for the treatment of various diseases including Diabetes Mellitus (DM) [3,4] . DM is mainly due to relatively low level of insulin production or an inability of the body to use insulin properly which, in turn, leads to hyperglycemia [5] .…”
Section: Introductionmentioning
confidence: 99%
“…This plant is also commonly known in Roman as Nettle and in Jordan as Qurraus [1,2] . For decades, crude extracts of plant species of U. pilulifera have long been used in many countries around the world as a traditional medicine for the treatment of various diseases including Diabetes Mellitus (DM) [3,4] . DM is mainly due to relatively low level of insulin production or an inability of the body to use insulin properly which, in turn, leads to hyperglycemia [5] .…”
Section: Introductionmentioning
confidence: 99%
“…9,21 By contrast, nettles have been used as a herbal remedy since antiquity, 5 and most of the medical Urtica literature concerns their use in conditions such as prostatism and colitis. 17,19 Lignans or steroids from Urtica roots may mediate effects on the prostate. 15,24 The water-soluble extract of U. dioica has been shown to have antioxidant properties, 13 and stimulates the proliferation of T-lymphocytes and suppresses nitric oxide (NO) production in lipopolysaccharide-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…There is contradictory evidence about the effectiveness of stinging nettle for symptoms of BPH. In one study, taking a combination product (PRO 160/120, Willmar Schwabe GmbH, Germany) containing a specific extract of stinging nettle (WS 1031) 120 mg plus a specific extract of saw palmetto (WS 1473) 160 mg twice daily for 24 weeks seemed to significantly improve urinary tract symptoms in men with BPH (Lopatkin et al, 2005). In another trial, an herbal product containing stinging nettle root extract 80 mg, saw palmetto lipoidal extract 106 mg, pumpkin seed oil extract 160 mg, lemon bioflavonoid extract 33 mg, and vitamin A (100% as beta-carotene) 190 IU taken three times daily for 6 months did not significantly improve symptoms of BPH (Marks et al, 2000).…”
Section: Nettle or Stinging Nettle (Urtica Dioica)mentioning
confidence: 99%
“…Nair B, 2001;Inoue et al, 2002 Allergic reactions and conjunctivitis (Paulsen, 2002;De Smet, 2002) Warfarin Citochrome P450 (Segal and Pilote, 2006) Nettle Osteoarthritis. BPH Allergic rhinitis (hayfever) (Mittman, 1990;Lopatkin et al, 2005) Uterine-stimulant effects, it can induce abortion (Heinrich, 2003;Gagnier et al, 2006) None reported…”
Section: Pepermintmentioning
confidence: 99%